Ecological Sustainability for “Life on Land”: Wellspring of Indigenous Knowledge - Léocadie Wabo Lushombo (Religions)
This article argues that indigenous knowledge is significantly resourceful for ecological sustainability, without which humanity will not survive. It addresses the intersection between the 15th United Nations Sustainable Development Goal (SGD) “Life on Land” and African indigenous knowledge systems, including the fundamental support system that can sustain the livelihoods of communities. It reconstructs the vision of ecological sustainability from the indigenous knowledge perspective by first analyzing the inadequacy of the United Nations carbon-pricing approach to reforestation and conservation in developing countries. Then, it uses the ethnosphere methodological approach, affirming the ecological ethical warrants found in indigenous epistemology and cosmology in regard to land protection in dialogue with the sustainability vision of Laudado Si’, Querida Amazonia, and Laudate Deum. This article explores indigenous knowledge’s wellspring for ecological sustainability and what it offers for a more sustainable “Life on Land”. It suggests an approach to ecological sustainability that goes beyond a market-based instrument to CO2 reduction to embrace a view of the “sacramental universe” as essential theological input, without which sustainable “Life on Land” cannot be met. It concludes by showing how African mountain region conservancy practices are not essential in sustaining “Life on Land” not solely because they provide the earth’s freshwater but also because they contain valuable ecologically sensitive cultural and religious wisdom.